The human cathelicidin hCAP‐18 in serum of children with haemato‐oncological diseases. (18th July 2022) - Jackmann, Natalja; Englund, Sofia; Frisk, Per; Mäkitie, Outi; Utriainen, Pauliina; Mörtberg, Anette; Henriques‐Normark, Birgitta; Pütsep, Katrin; Harila‐Saari, Arja
Summary: The human cathelicidin hCAP‐18 (pro‐LL‐37) is the pro‐protein of the antimicrobial peptide LL‐37. hCAP‐18 can be produced by many different cell types; bone marrow neutrophil precursors are the main source of hCAP‐18 in the circulation. Neutrophil count is used as a marker for myelopoiesis but does not always reflect neutrophil production in the bone marrow, and thus additional markers are needed. In this study, we established the reference interval of serum hCAP‐18 level in healthy children and compared serum hCAP‐18 levels between different diagnostic groups of children with haemato‐oncological diseases, at diagnosis. We found that children with diseases that impair myelopoiesis, such as acute leukaemia, aplastic anaemia, or myelodysplastic syndrome, presented with low hCAP‐18 levels, whereas patients with non‐haematological malignancies displayed serum hCAP‐18 levels in the same range as healthy children. Children with chronic myeloid leukaemia presented with high circulating levels of hCAP‐18, probably reflecting the high number of all differentiation stages of myeloid cells. We suggest that analysis of serum hCAP‐18 provides additional information regarding myelopoiesis in children with haemato‐oncological diseases, which may have future implications in assessment of myelopoiesis in clinical management.